1985
DOI: 10.1149/1.2113572
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of Reductants in Electroless Plating

Abstract: The anodic oxidation of reductants (hypophosphite, formaldehyde, borohydride, dimethylamine borane, and hydrazine) was studied on different metal electrodes (Au, Pt, Pd, Ag, Cu, Ni, and Co) at various temperatures, with special interest in the catalytic aspect of electroless plating. The rate of the anodic oxidation strongly depended on the pH value, the concentration of reductants, and the nature of the metal electrode. The catalytic activities of the metals for the anodic oxidation of different reductants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
190
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(203 citation statements)
references
References 20 publications
10
190
1
2
Order By: Relevance
“…Ni has been shown to exhibit a lower borane oxidation rate capability than Pd at the potentials of electroless plating baths [19]. It is expected, therefore, that the deposition rate would decrease during nanotube growth.…”
mentioning
confidence: 99%
“…Ni has been shown to exhibit a lower borane oxidation rate capability than Pd at the potentials of electroless plating baths [19]. It is expected, therefore, that the deposition rate would decrease during nanotube growth.…”
mentioning
confidence: 99%
“…It has previously been proved that copper does not have catalytic activity for the oxidation of hypophosphite by experimental identification. 19 M. Kunimoto et al have also demonstrated 3 that an energy barrier exists in the dehydrogenation step which is one of the elementary steps of hypophosphite oxidation by theoretical identification. Figure 4 shows the experimental Raman spectra of mixture (hydrazine and hypophosphite) on the Cu antenna.…”
Section: Resultsmentioning
confidence: 98%
“…More specifically, Pd surfaces display strong catalytic activity on hypophosphite reactions, whereas Cu surfaces show only weak activity. 23 Hence, comparing the reaction on Pd with that on Cu allows the identification of factors that determine their catalytic activity.…”
Section: Methodsmentioning
confidence: 99%